2015
DOI: 10.1007/s13277-015-4360-8
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA MVIH is associated with poor prognosis and malignant biological behavior in breast cancer

Abstract: In recent years, with the development of transcriptomics, the effect of long non-coding RNAs (LncRNAs) on the regulation of biological processes is being elucidated. LncRNAs play an important role in tumor occurrence and development. LncRNA associated with microvascular invasion in hepatocellular carcinoma (LncRNA MVIH) was first identified in hepatocellular carcinoma and is associated with angiogenesis, tumor growth and metastasis upregulation, and poor recurrence-free survival. MVIH has an important role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 23 publications
0
47
0
1
Order By: Relevance
“…[10][11][12][13][14] For instance, some studies display that lncRNA MVIH expression is elevated in HCC tissues as well as breast cancer tissues than that in adjacent non-cancerous tissues. 11,14 Additionally, a study discloses that lncRNA MVIH expression is positively correlated with Karnofsky performance score and World Health Organization (WHO) grade in glioma patients. 10 The predictive role of lncRNA MVIH for prognosis in solid tumors has also been disclosed in some clinical practices.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[10][11][12][13][14] For instance, some studies display that lncRNA MVIH expression is elevated in HCC tissues as well as breast cancer tissues than that in adjacent non-cancerous tissues. 11,14 Additionally, a study discloses that lncRNA MVIH expression is positively correlated with Karnofsky performance score and World Health Organization (WHO) grade in glioma patients. 10 The predictive role of lncRNA MVIH for prognosis in solid tumors has also been disclosed in some clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…10 The predictive role of lncRNA MVIH for prognosis in solid tumors has also been disclosed in some clinical practices. [10][11][12] For instance, lncRNA MVIH high expression is associated with poor disease-free survival and OS in breast cancer patients. 11 Also, lncRNA MVIH high To explore how lncRNA MVIH regulate cell activities in cancers, some in vitro or in vivo experiments are conducted by previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, lncRNA MVIH was found to be significantly upregulated in breast cancer tissues than in adjacent noncancerous tissues, and patients with high MVIH levels showed poor overall survival and disease-free survival (Lei et al 2016). In vitro study revealed that MVIH could promote cell proliferation and cell cycle, while inhibiting apoptosis of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%